Exploring the Interplay of Listening, Articulation, and Arabic Language Proficiency among Children in Pesantren - Akla, Akla; Arifin, Ahmad (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2024)
This study aims to analyze the level of Arabic listening and articulation skills and their relationship with Arabic language skills among non-native speakers in children's boarding schools in Lampung Province. The research approach was correlational. The research participants were children of boarding students at Hidayatul Qur'an Islamic Boarding School, Darussalam Islamic Boarding School, and Al-Imam Islamic Boarding School, Lampung Province. The selected respondents were children aged 7-9 years. The data collection instrument was a test. The research findings show the significant value of listening and articulation skills based on gender, age, Qur'an learning experience, the number of memorized Qur'an owned, parental income, and geographical area of residence is 0.000 <0.05. This value demonstrates the significant influence of these variables on children's listening and articulation skills. The analysis results show that the correlation coefficient of the listening ability and articulation ability variables is 0.370 and 0.621, which means that the strength of the relationship between each variable and Arabic language skills has sufficient and robust criteria. Both values are positive, showing that the effect is unidirectional. The significance values of 0.873 and 0.015> 0.05 show positive signs, meaning a significant relationship exists between listening ability and articulation with Arabic language skills. This means the rise will follow increased listening and articulation ability variables in children's Arabic language skills. The calculation result of the coefficient of determination or R square value is 0.725. This implies that listening ability and articulation affect the Arabic language proficiency variable by 72.5%. Other variables might influence the remaining percentage.